Development of Cadmium Multiple-Signal Biosensing and Bioadsorption Systems Based on Artificial Cad Operons - Guo, Yan; Hui, Chang-ye; Zhang, Nai-xing; Liu, Lisa; Li, Hui; Zheng, Hong-ju (Frontiers in Bioengineering and Biotechnology, 2021)
The development of genetic engineering, especially synthetic biology, greatly contributes to the development of novel metal biosensors. The cad operon encoding cadmium resistance was previously characterized from Pseudomonas putida. In this study, single-, dual-, and triple-signal output Cd(II) biosensors were successfully developed using artificial translationally coupled cad operons. Sensitivity, selectivity, and response towards Cd(II) and Hg(II), of three biosensors were all determined. Reporter signals of three biosensors all increased within the range 0.1-3.125 μM Cd(II). Three biosensors responded strongly to Cd(II), and weakly to Hg(II). However, the detection ranges of Cd(II) and Hg(II) do not overlap in all three biosensors. Next, novel Cd(II) biosensing coupled with bioadsorptive artificial cad operons were assembled for the first time. Cd(II)-induced fluorescence emission, enzymatic indication, and Cd(II) binding protein surface display can be achieved simultaneously. This study provides an example of one way to realize multiple signal outputs and bioadsorption based on the redesigned heavy metal resistance operons, which may be a potential strategy for biodetection and removal of toxic metal in the environment, facilitating the study of the mechanism and dynamics of bioremediation.